Evaluation recommendations for nonprofit social marketing campaigns: An example from the Louisiana Campaign for Tobacco‐Free Living. Issue 1 (29th December 2016) - Rudov, Lindsey; McCormick‐Ricket, Iben; Kingsmill, Dustin; Ledford, Cannon; Carton, Thomas
Abstract : Nonprofit organizations with limited capacity and resources must be strategic when designing, implementing, and evaluating social marketing campaigns. The Louisiana Campaign for Tobacco‐Free Living, a nonprofit public health program, implemented a mass media campaign in 2012, with the goal of increasing advocacy for policy change around the smoke‐free movement. The campaign was accompanied by a mixed–quantitative evaluation that was grounded in the diffusion of innovations theory. The evaluation consisted of unique, yet complementary, analytical components, employing traditional survey methods to measure population exposure to the campaign and Google Analytics to segment campaign website visitors into actionable categories for future programmatic efforts. Results from this study demonstrate that the 2012 Tobacco‐Free Living mass media campaign was moderately effective in reaching its target audience and highly effective in using Google Analytics to identify a group of activists (i.e., innovators) in support of the smoke‐free policy change. This study offers several recommendations for nonprofit organizations to consider when implementing and evaluating similar social marketing campaigns.